2013
DOI: 10.1002/btpr.1683
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of tosyl‐activated magnetic and nonmagnetic monodisperse microspheres for use in microfluic‐based ferritin immunoassay

Abstract: This article describes the preparation of tosyl-activated nonmagnetic poly(2-hydroxyethyl methacrylate-co-glycidyl methacrylate) [P(HEMA-GMA)] microspheres by dispersion polymerization and tosyl-activated magnetic poly(2-hydroxyethyl methacrylate-co-ethylene dimethacrylate) [P(HEMA-EDMA)] microspheres by multistep swelling polymerization method and precipitation of iron oxide inside the pores. These new approaches show that monodisperse microspheres, 2.3 µm, respectively 4.1 µm, in diameter can be produced in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Various polymerimmobilizations to particle surfaces, have been reported in order to achieve biological goals. 3,[11][12][13][14][15][16][17] The advantage of attaching amino-dextran to micro/nanoparticles for ATPS is to give the target particles more affinity to dextran-rich phase, which is located at the bottom of two layers (The top layer of ATPS, PEG-rich phase is more hydrophobic. Also the bottom layer, DEX-rich phase is more hydrophilic and dense).…”
Section: Ir Spectral Investigation Of Amino-dextran (Adex) Modified Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Various polymerimmobilizations to particle surfaces, have been reported in order to achieve biological goals. 3,[11][12][13][14][15][16][17] The advantage of attaching amino-dextran to micro/nanoparticles for ATPS is to give the target particles more affinity to dextran-rich phase, which is located at the bottom of two layers (The top layer of ATPS, PEG-rich phase is more hydrophobic. Also the bottom layer, DEX-rich phase is more hydrophilic and dense).…”
Section: Ir Spectral Investigation Of Amino-dextran (Adex) Modified Mmentioning
confidence: 99%
“…6,7 Wide and various applications on IR spectroscopy cover even the confirmation of bacterial attachment and changes on particles 3,8,9 and IR spectroscopy is still considered as one of the most widely used and reliable methods for chemical changes at the surface of materials. 3,6,7,[10][11][12][13][14][15]17,18 Here the infrared (IR) microscopic investigation results to prove the surface modification of polystyrene (PS)-coated magnetic microparticles, are reported. .…”
Section: Introductionmentioning
confidence: 99%
“…PGMA microspheres are of growing interest for various biotechnological applications (Reymond et al ., ). They were successfully used for immobilization of α ‐amylase (He et al ., ) and catalase (Bayramoglu et al ., ), as well as enzyme stabilization (Milosavić and Prodanović, ), for binding of hemoglobin from human blood hemolysate (Altıntas et al ., ), adsorption and separation of immunoglobulins (Bayramoglu et al ., ), and ion exchange chromatographic separation of other proteins (Unsal et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The work by Reymond et al on a microfluidic-based ferritin immunoassay used an eight channel electrochemical microchip modified with magnetic and non-magnetic microspheres for antibody immobilization. However, the research did not cover the required clinical range of ferritin quantification [43]. In another article by Song et al, the use of cotton thread as a microfluidic circuit was suggested, where three sets of antibodies were used in the sensor fabrication.…”
Section: Electrochemical Detection Of Ferritin and Sensor Performancementioning
confidence: 99%